Biomimetic Human Tissue Model for Long-Term Study of Neisseria gonorrhoeae Infection - Heydarian, Motaharehsadat; Yang, Tao; Schweinlin, Matthias; Steinke, Maria; Walles, Heike; Rudel, Thomas; Kozjak-Pavlovic, Vera (Frontiers in Microbiology, 2019)
Gonorrhea is the second most common sexually transmitted disease in the world and is caused by Gram-negative diplococcus Neisseria gonorrhoeae. Since N. gonorrhoeae is a human-specific pathogen, animal infection models are only of limited use. Therefore, a suitable in vitro cell culture model for studying the complete infection including adhesion, transcytosis and transport to deeper tissue layers is required. In the present study, we generated three independent 3D tissue models based on porcine small intestinal submucosa (SIS) scaffold by co-culturing human dermal fibroblasts with human colorectal carcinoma, endometrial epithelial, and male uroepithelial cells. Functional analyses such as transepithelial electrical resistance (TEER) and FITC-dextran assay indicated the high barrier integrity of the created monolayer. The histological, immunohistochemical and ultra-structural analyses showed that the 3D SIS scaffold-based models closely mimic the main characteristics of the site of gonococcal infection in human host including the epithelial monolayer, the underlying connective tissue, mucus production, tight junction and microvilli formation. We infected the established 3D tissue models with different N. gonorrhoeae strains and derivatives presenting various phenotypes regarding adhesion and invasion. The results indicated that the disruption of tight junctions and increase in interleukin production in response to the infection is strain and cell type-dependent. In addition, the models supported bacterial survival and proved to be better suitable for studying infection over the course of several days in comparison to commonly used Transwell® models. This was primarily due to increased resilience of the SIS scaffold models to infection in terms of changes in permeability, cell destruction and bacterial transcytosis. In summary, the SIS scaffold-based 3D tissue models of human mucosal tissues represent promising tools for investigating N. gonorrhoeae infections under close-to-natural conditions.